Adoption of Target Costing in Diverse Industries: A Qualitative Study - Alam, Mahjabeen Binte; Ahmed, Tanvir; Khan, Zahin Irfan; Haque, Masnun; Hera, Shehrly Mahboob (International Journal of Business Strategy and Social Sciences, 2020)
The motive of this paper is to review the articles and research papers regarding the adoption of target costing in different sectors and examines several findings and gaps in the existing literature. This paper reviews existing literature from some renowned journals, official associations and published researches from various timelines. Review of eighteen-journal paper related to target costing is included in this paper. Implication of target costing is the main point of the papers, which is included. Target costing is a popular concept, which is proved to bring better result if applied in the earlier design stages and if firms have a good coordination among their various departments. The papers mostly tested manufacturing firms and construction firms. The findings of the paper suggest that most of the companies do not consider any particular policy for target costing even though these are from same type of industries. Target costing related papers are hard to find in Bangladesh and this paper attempts to give an overall review on the major findings from its adoption. It discovers some gaps in the current existing literature and requires further researches on its application on various other industries.